Stroll’n’Draw, All Inclusive. Let us embrace contingency to visualise and to reinforce the uniqueness of places. - Fritsche, Niels-Christian (My University, 2020)
In this paper, I discuss the education of inclusive urbanism as the inclusionof the environmental awareness genesis, attitudes toward urban design,cognitive biases and the acceptance of contingency. How do places ‘happen’to become what they are? What characterises their potentially unreduciblesingularity in light of general planning laws?I suggest educating along a didactic triangle of rules, novelty and singularityin a spatialisable tabular fashion. In addition to using the methods presentedhere in teaching, these approaches can also be used to create more inclusionin urban development processes as a whole. With a 3D visualisation matrixof analogue, hybrid and digital methods, I proceed to four exemplary multimethodologicalteaching modes to tackle the ever-bygone status quo, tointroduce research methodology and, thereby, the defeasibility of both thepremises and the conclusions in all-too traditional urban design.I focus on abductive reasoning between the unique locality and the generalspace of possibility as trial acting and “plan-b thinking” to dialectically shuttlewithin didactic triangle and visualisation matrix. The curriculum allows forprincipal and exemplary multi-methodological cross-linkage. Open projectsserve as stepping stones into the broad variety of non-algorithmic humanoccupations in 21st century urban planning. Let us understand our ownmultiple personal urbanites way beyond professional applicability.
Keywords: Urbanistik; Stadtplanung; Integrierte Stadtentwicklung; Inklusion; Planerausbildung; Raumplanerausbildung; Planungsverständnis; Raumtheorie; Raumwahrnehmung; Visualisierung; Spaziergangswissenschaft